Determinan Profitabilitas Bank Umum Syariah di Indonesia Tahun 2017-2021 - Lina Malikhatun; Dahlia Tri Anggraini (STES Islamic Village, 2023)
This study examines the influence of Capital Adequacy Ratio (CAR) and Financing to Deposit Ratio (FDR) on the profitability of Islamic banks in Indonesia from 2017 to 2021, with a particular focus on the moderating role of Non-Performing Financing (NPF). Utilizing a quantitative research approach, the study analyzes secondary data obtained from annual reports of six selected Islamic banks through a purposive sampling method. The dataset comprises a total of 30 annual reports. Employing Moderated Regression Analysis (MRA) with SPSS version 25, the findings indicate that neither CAR nor FDR significantly affect profitability in the selected Islamic banks. Moreover, NPF is found to have an insignificant impact on profitability. However, it is noteworthy that NPF does not act as a moderator in the relationship between CAR and profitability. Conversely, NPF is found to moderate the association between FDR and profitability. These results shed light on the specific context of Indonesian Islamic banks during the studied period. The lack of a significant influence of CAR and FDR on profitability suggests that these factors may not be the primary drivers of profitability in Islamic banks. Nonetheless, the observed moderating effect of NPF on the relationship between FDR and profitability highlights the importance of credit quality in shaping bank profitability. The implications of these findings extend to regulatory authorities, bank management, and stakeholders, who can utilize them to develop strategies for enhancing the performance of Islamic banks in Indonesia. Nevertheless, it is essential to acknowledge the limitations of this study, such as the small sample size and the restriction to a specific time frame and geographical location. Thus, caution is warranted when generalizing these findings to other Islamic banks or different time periods. Future research endeavors may explore additional variables and expand the scope of the study to gain a more comprehensive understanding of the factors impacting profitability in Islamic banks.